Barton-Jenifer family papers
Correspondence, dispatches, bills, patents, Confederate paper money, and a copy of "The Deposition of Ann Taft" (1663). Persons represented in the Barton correspondence include Seth Barton, Baltimore merchant; Seth Maxwell Barton (1829-1900), Confederate soldier; Franklin Buchanan; Henry R. Jackson; Stonewall Jackson;, and Daniel Webster. Persons represented in the Jenifer correspondence include Daniel of St. Thomas Jenifer (1723-1790); Daniel Jenifer (1791-1855), U.S. representative from Maryland and diplomat; Walter Jenifer (d. 1878), Confederate soldier; P. G. T. Beauregard; Franklin Buchanan; James Buchanan; Charles Carroll; Henry Clay; Joseph R. Ingersoll; and Joseph E. Johnston.
In part, transcript.
Collection material in English.
Keywords: Barton, Seth -- Correspondence; Barton, Seth Maxwell, -- 1829-1900 -- Correspondence; Beauregard, G. T. -- 1818-1893 -- Correspondence; Buchanan, Franklin, -- 1800-1874 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Carroll, Charles, -- 1723-1783 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Ingersoll, Joseph R. -- 1786-1868 -- Correspondence; Jackson, Henry R. -- 1820-1898 -- Correspondence; Jackson, Stonewall, -- 1824-1863 -- Correspondence; Jenifer, Daniel, -- 1791-1855 -- Correspondence; Jenifer, Daniel of St. Thomas, -- 1723-1790 -- Correspondence; Jenifer, Walter, -- -1878 -- Correspondence; Johnston, Joseph E. -- 1807-1891 -- Correspondence; Taft, Ann; Webster, Daniel, -- 1782-1852 -- Correspondence; Maryland -- Politics and government; Jenifer family; Barton family; Diplomats; Merchants; Representatives, U.S. Congress -- Maryland; Soldiers